What Engineering Sophomores Know and Would Like to Know About Engineering Information Sources and Access. - Zorana Ercegovac (Issues in Science and Technology Librarianship)
This exploratory study reports on what engineering undergraduate students know and would like to learn about engineering information sources and access. Responses were obtained on selected performance measures within the framework of Information Literacy Standards for Science and Engineering/Technology (ACRL/ALA/STS 2006). The results are based on 70 sophomores who completed a four-page paper-and-pencil questionnaire on April 4, 2008 at UCLA's School of Engineering and Applied Sciences. The paper discusses implications of this study's findings in light of engineering education in general, and specifically with regard to instructing all engineering students in the proper use of a variety of pathways in accessing high quality engineering resources for numerous lifelong purposes.